Four novel variants identified in primary hyperoxaluria and genotypic and phenotypic analysis in 21 Chinese patients - Xin, Qing; Dong, Yameng; Guo, Wencong; Zhao, Xiangzhong; Liu, Zhiying; Shi, Xiaomeng; Lang, Yanhua; Shao, Leping (Frontiers in Genetics, 2023)
Abstract Background: Primary hyperoxaluria (PH) is a rare genetic disorder characterized by excessive accumulation of oxalate in plasma and urine, resulting in various phenotypes due to allelic and clinical heterogeneity. This study aimed to analyze the genotype of 21 Chinese patients with primary hyperoxaluria (PH) and explore their correlations between genotype and phenotype. Methods: Combined with clinical phenotypic and genetic analysis, we identified 21 PH patients from highly suspected Chinese patients. The clinical, biochemical, and genetic data of the 21 patients were subsequently reviewed. Results: We reported 21 cases of PH in China, including 12 cases of PH1, 3 cases of PH2 and 6 cases of PH3, and identified 2 novel variants (c.632T > G and c.823_824del) in AGXT gene and 2 novel variants (c.258_272del and c.866-34_866-8del) in GRHPR gene, respectively. A possible PH3 hotspot variant c.769T> G was identified for the first time. In addition, patients with PH1 showed higher levels of creatinine and lower eGFR than those with PH2 and PH3. In PH1, patients with severe variants in both alleles had significantly higher creatinine and lower eGFR than other patients. Delayed diagnosis still existed in some late-onset patients. Of all cases, 6 had reached to end-stage kidney disease (ESKD) at diagnosis with systemic oxalosis. Five patients were on dialysis and three had undergone kidney or liver transplants. Notably, four patients showed a favorable therapeutic response to vitamin B6, and c.815-816insGA and c.145A> C may be identified as potentially vitamin B6-sensitive genotypes. Conclusions: In brief, our study identified 4 novel variants and extended the variant spectrum of PH in the Chinese population. The clinical phenotype was characterized by large heterogeneity, which may be determined by genotype and a variety of other factors. We first reported two variants that may be sensitive to vitamin B6 therapy in Chinese population, providing valuable references for clinical treatment. In addition, early screening and prognosis of PH should be given more attention. We propose to establish a large-scale registration system for rare genetic diseases in China and call for more attention on rare kidney genetic diseases.